2021
DOI: 10.1177/10870547211017985
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Impairment on the Prevalence and Comorbidities of Attention Deficit Hyperactivity Disorder in a National Survey: Nation-Wide Prevalence and Comorbidities of ADHD

Abstract: Objective: This study aimed to determine the prevalence and comorbidities of attention-deficit hyperactivity disorder (ADHD) by evaluating a large-scale nation-wide sample of children. Method: The inclusion criterion was being enrolled as a 2nd, 3rd, or 4th-grade student. A semi-structured diagnostic interview (K-SADS-PL), DSM-IV-Based Screening Scale for Disruptive Behavior Disorders, and assessment of impairment (by both parents and teachers) were applied to 5,842 participants. Results: The prevalence of ADH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…Recent estimates indicate that the prevalence of ADHD diagnosis is 12.4% among Turkish students aged 8-10 years, representing a significantly higher prevalence than the worldwide trend (i.e., 3.4%; Ercan et al, 2022;Polanczyk et al, 2015). Students with ADHD display chronic behavior difficulties in school settings, such as being out of seat, breaking classroom rules, making inappropriate noises, and calling out without permission (Barkley, 2015;DuPaul & Jimerson, 2014;Dupoul & Stoner, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Recent estimates indicate that the prevalence of ADHD diagnosis is 12.4% among Turkish students aged 8-10 years, representing a significantly higher prevalence than the worldwide trend (i.e., 3.4%; Ercan et al, 2022;Polanczyk et al, 2015). Students with ADHD display chronic behavior difficulties in school settings, such as being out of seat, breaking classroom rules, making inappropriate noises, and calling out without permission (Barkley, 2015;DuPaul & Jimerson, 2014;Dupoul & Stoner, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, there is a knowledge gap in the context of Turkish teachers that has been attempted to be filled by a limited number of studies [ 15 ]. This gap is particularly concerning given that a recent nationwide study in Turkey reported a higher prevalence of ADHD among children in the second to fourth grades (19.5% without impairment and 12.4% with impairment) than the global average [ 16 ]. Moreover, children with ADHD in Turkey may miss out on the free support and educational resources available to them due to the underdiagnosis of ADHD.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of ADHD was found 11% in children and adolescent [1]. In a multi-center study conducted in Turkey included 5830 children, the prevalence of ADHD was found 12.4 % [2]. ADHD symptoms continue in adolescence and adulthood in 40-60% of those diagnosed with ADHD in childhood [3,4].…”
Section: Introductionmentioning
confidence: 99%